Attention-deficit/hyperactivity disorder: variation by socio-economic deprivation - Prasad, Vibhore; West, Joe; Kendrick, Denise; Sayal, Kapil (BMJ Publishing Group, 2018)
Background: In England, there is a discrepancy between the prevalence of Attention-deficit/hyperactivity disorder (ADHD) ascertained from medical records and community surveys. There is also a lack of data on variation in recorded prevalence by deprivation and geographical region; information that is important for service development and commissioning.